Surveillance of tuberculosis in Spain, 2023 (Boletín Epidemiológico Semanal, 2025)
Introduction: The objective of this study was to describe the epidemiological situation of tuberculosis (TB) in Spain during the year 2023 and its temporal evolution since 2015.Method: Descriptive analysis of TB cases reported by the CCAA to the National Epidemiological Surveillance Network (RENAVE). The variables analysed were: sex, age, Autonomous Community, country of birth, date of case, location, co-infection with HIV, treatment outcome, death and antituberculostatic resistance. Notification rates were calculated and a time-space study was carried out based on these rates.Results: In 2023, a total of 3,944 autochthonous TB cases were reported (notification rate of 8.2 per 100,000 population). The % of cases was higher in men (2,575 cases, 65.3%) and the main location was pulmonary (n=2,721.69%). In 78.6% of the cases in which the treatment outcome was reported to be satisfactory. The ratio born in Spain/born in another country showed a progressive decrease between 2015 and 2023 (from 2.2 to 1.1, respectively). There was a 7% increase in notification rates compared to 2022 and a 22.5% decrease compared to 2015.This decreasing trend in rates was observed in most of the CCAA. The decrease was more pronounced for pulmonary forms. Discussion: The profile of cases shows no significant variation, except in relation to country of birth. The TB notification rate declined from 2015 to 2023, especially in pulmonary forms, although the rate of decline does not seem sufficient to reach the targets defined in the WHO End TB Strategy.
Keywords: Tuberculosis; Surveillance; RENAVE